Formation and consolidation of the monarchical bishopric: debates and interpretations about the role of the bishop in Late Antiquity - Soares, Carolline da Silva (Romanitas - Revista de Estudos Grecolatinos, 2017)
Review of: ACERBI, S.; MARCOS, M.; TORRES, J. (Ed.). El obispo en la Antigüedad Tardia: homenaje a Ramón Teja. Madrid: Editorial Trotta, 2016. 364 p.